Fucoidan from Vietnam Sargassum swartzii: Isolation, Characterization and Complexation with Bovine Serum Albumin - Thi Thu Thuy, Thanh; Thi Thanh Van, Tran; Hidekazu, Yasunaga; Hiroshi, Urakawa (Asian Journal of Chemistry, 2012)
Many brown seaweeds of Sargassum genus such as S. polycystum, S. mcclurei, S. oligocystum, S. denticarpum, S. swatzii are available in Nha-Trang bay of Vietnam. The structural characteristics of polysaccharides extracted from Vietnam's brown seaweed have not been fully established up to now. In this work, a fucoidan was extracted from brown seaweed Sargassum swartzii harvested at Nha-trang bay of Vietnam, the yield was 0.68 % (w/w) based on the dry seaweed. The uronic acid and sulfate content were obtained 6.3 % and 24.7 % of dried weight, respectively. The molar ratio of sugar residues was estimated to be fucose:galactose:mannose:xylose:glucose = 3.6:3.2:1.9:1:0.3 by gas chromatography. By using static and dynamic light scattering methods, conformation of fucoidan and its complex with bovine serum albumin at different pH environment were observed. The results showed that overall conformation of fucoidan is rigid rod. At pH value of 7.4, interaction between fucoidan and bovine serum albumin was very weak and conformation of native albumin was maintained. At pH value of 4.0 the interaction becomes strong, this is an electrostatic interaction occurred between sulfate groups of fucoidan and binding site in bovine serum albumin and a complex between fucoidan and bovine serum albumin forms very quickly and the complex has a spherical structure.